Home » Solve for r in the following equation (frac{1}{r – 1}) + (frac{2}{r + 1}) =…

Solve for r in the following equation (frac{1}{r – 1}) + (frac{2}{r + 1}) =…

Solve for r in the following equation (frac{1}{r – 1}) + (frac{2}{r + 1}) = (frac{3}{r})
  • A.
    3
  • B.
    4
  • C.
    5
  • D.
    6
Correct Answer: Option A
Explanation

(frac{1}{r – 1}) + (frac{2}{r + 1}) = (frac{3}{r})
Multiply through by r(r -1) which is the LCM
= (r)(r + 1) + 2(r)(r – 1)
= 3(r – 1)(r + 1)
= r2 + r + 2r2 – 2r
3r2 – 3 = 3r2
r = 3r2 – 3
-r = -3
∴ r = 3